The Influence of Transformational Leadership on Innovative Work Behavior with Employee Motivation and Knowledge Sharing As Mediation in the Government of Aceh Jaya District - Khizzir, Muhammad; Amri,; Halimatussakdiah, (International Journal of Scientific Research and Management (IJSRM), 2025)
The purpose of this study is to examine the extent to which the influence of transformational leadership on innovative work behavior with employee motivation and knowledge sharing as mediation in the Government of Aceh Jaya District. The study population comprised all civil servants within the Aceh Jaya District Government, totaling 498 individuals. A sample of 190 civil servants was selected for analysis. Data were analyzed using the Structural Equation Modeling approach with AMOS software. The findings reveal that transformational leadership has a significant positive effect on innovative work behavior among employees. Moreover, transformational leadership significantly influences both employee motivation and knowledge sharing. In turn, employee motivation and knowledge sharing each have a significant impact on innovative work behavior. Mediation analysis shows that both employee motivation and knowledge sharing partially mediate the relationship between transformational leadership and innovative work behavior.